Political instability and political terror - Asongu, Simplice,Uduji, Joseph I.,Okolo-Obasi, Elda N. (African Governance and Development Institute, 2020)
We test the hypotheses that fundamental characteristics in regional proximity, landlockedness, religious-domination, legal origin, and income levels affect cross-country differences in the persistence in political terror and political instability in 163 countries for the period 2010 to 2015. The empirical evidence is based on Generalised Method of Moments. The hypotheses are that the following are associated with comparatively higher levels of persistence in political terror and political instability: regions with predominantly low income countries (Hypothesis 1); landlockedness (Hypothesis 2); Christian-orientation (Hypothesis 3); French civil law (Hypothesis 4) and Low income (Hypothesis 5). The tested hypotheses are largely invalid. Only Hypothesis 5 and Hypothesis 2 are robustly investigated in the light of concerns about instrument proliferation. Hypothesis 2 is valid for political terror but not for political instability while Hypothesis 5 is neither valid for political instability nor for political terror.
10419/227994
Keywords: Graue Literatur; political instability; political terror; economic development; comparative studies